Makna Seksualitas Perempuan dalam Qs. Yusuf Ayat 23-32 Melalui Kisah Nabi Yusuf dan Zulaikha - Siti Asiah; Jannatul Aini (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2024)
This study reconstructs the meaning of female sexuality in QS. Yusuf verses 23–32 through a feminist epistemological reading of the Zulaikha narrative. Classical Qur'anic exegesis has predominantly framed Zulaikha as a morally deficient seductress, reproducing patriarchal stereotypes that reduce women to passive objects of male desire while obscuring the socio-cultural and power structures shaping her actions. Employing a qualitative library research method with a descriptive-analytical approach grounded in feminist epistemology (standpoint, empiricism, and postmodernism), this study analyzes classical and contemporary tafsir works alongside gender studies literature. The findings demonstrate that Zulaikha cannot be positioned solely as a transgressor; rather, her actions must be read within the context of an asymmetrical marital relation marked by sexual deprivation, verbal neglect, and structural patriarchal domination by al-Aziz. The novelty of this study lies in proposing an integrated reading framework that combines feminist epistemology with classical tafsir, repositioning female sexuality in the Qur'an not as taboo but as part of human nature regulated ethically and spiritually. This reinterpretation contributes to the development of gender-just Qur'anic exegesis relevant to contemporary discourse on women, agency, and religious authority.